Home-versus acquired-language test performance on the Hopkins Verbal Learning Test-Revised among multilingual South Africans. Issue 2 (3rd March 2020) - Scott, Travis M.; Gouse, Hetta; Joska, John; Thomas, Kevin G. F.; Henry, Michelle; Dreyer, Anna; Robbins, Reuben N.
Abstract: The Hopkins Verbal Learning Test-Revised (HVLT-R) has been adapted for use in many different languages and in low- and middle-income countries. However, few adaptations have evaluated performance differences between home- and acquired-language administrations. The present study examined performance on an adapted HVLT-R between multilingual South Africans who chose to be tested in a home or acquired language. The HVLT-R was administered to 112 multilingual, isiXhosa as home language, Black South African adults (49% men) with no major medical, neurological, or psychiatric problems. Sixty-one preferred to take the test in isiXhosa and 51 preferred English. We examined between-language differences in word equivalency, primary scores, learning indices, and serial position effects. We also examined language, age, education, and gender on test performance. English-examinees were significantly younger and more educated than isiXhosa-examinees ( p 's < .05). Although isiXhosa words had more letters and syllables than English words ( p 's <.001), there were no significant differences between groups on HVLT-R performance or serial recall ( p 's > .05). More education and being a woman predicted better Total and Delayed Recall ( p 's<.05). Performance on this modified HVLT-R appears similar between English and isiXhosa administrations among South African isiXhosa first language speakers, which makes comparisons between preferred language administrations appropriate.